2020
DOI: 10.25126/jtiik.2020701662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Heuristik Website berbasis Framework Sirius dengan Pengaturan Prioritas menggunakan Teknik Moscow

Abstract: <p class="Abstrak">Kualitas merupakan faktor utama kesuksesan sebuah website. Salah satu karakteristik kualitas perangkat lunak menurut ISO 9126 adalah usabilitas. Pengukuran usabilitas sebuah website adalah hal yang penting mengingat sangat besarnya jumlah website saat ini. Salah satu metode yang dapat digunakan untuk mengevaluasi usabilitas website adalah <em>framework</em> Sirius. Sirius dapat menghasilkan nilai usabilitas global dan daftar elemen antarmuka sistem yang perlu diperbaiki. Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…However, from the results of the analysis, it was concluded that only about 5% of the usability criteria were mutually agreed upon by all evaluators as an issue that must be fixed by the website building team. Research related to the Sirius framework and the Moscow technique was carried out by [11] conducting usability evaluations for three websites, namely Lective, Seminar Indonesia and SIMKESMAS. Based on the results of the evaluation of the usability value for Lective, it was 63.56%, for the Indonesian Seminar it was 69.61% and for SIMKESMAS it was 57.65%, so it can be concluded that the three websites were in a proper condition.…”
Section: Related Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…However, from the results of the analysis, it was concluded that only about 5% of the usability criteria were mutually agreed upon by all evaluators as an issue that must be fixed by the website building team. Research related to the Sirius framework and the Moscow technique was carried out by [11] conducting usability evaluations for three websites, namely Lective, Seminar Indonesia and SIMKESMAS. Based on the results of the evaluation of the usability value for Lective, it was 63.56%, for the Indonesian Seminar it was 69.61% and for SIMKESMAS it was 57.65%, so it can be concluded that the three websites were in a proper condition.…”
Section: Related Researchmentioning
confidence: 99%
“…Based on previous research, this research examines the usability of an information system related to lecturers at an information technology-based university using the Sirius Framework and the Moscow Technique. The differences of this research from research by [11] where the expert is a lecturer with knowledge related to usability and system development directly interact or have used SID. By using the evaluator, it is hoped that the evaluation results will improve the accuracy of the evaluation, namely to produce the most urgent criteria order and a priority list of improvement criteria according to real conditions.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…User story dikategorikan kedalam 4 kategori prioritas yaitu, Must Have, Should have, Could have, Won't Have [9]. Kategori tersebut digunakan untuk menentukan kebutuhan yang harus diimplementasikan dan kebutuhan yang merupakan pelengkap.…”
Section: Metode Moscowunclassified